Data from: The earliest baleen whale of the mediterranean: Large-scale implications of an early miocene thalassotherian mysticete from Piedmont, Italy - Bisconti, Michelangelo; Damarco, Piero; Mao, Selina; Pavia, Marco; Carnevale, Giorgio (Zenodo, 2020)
The discovery of an Early Miocene chaeomysticete from the Pietra da Cantoni Group in Piedmont (north-western Italy) allowed for the creation of Atlanticetus n. gen. and Atlanticetus lavei n. sp. The new species is represented by a partial skeleton including the earbones and shows anatomical resemblance with Atlanticetus patulus (new combination) from the western North Atlantic. The Early Miocene age of the new specimen supports the view that it represents the oldest record of Chaeomysticeti from the Mediterranean. A new phylogenetic analysis showed that both A. patulus and A. lavei belong to a radiation of basal thalassotherian taxa. The basal thalassotherians are found being monophyletic to the exclusion of Cetotheriidae and Balaenopteroidea. The reconstruction of ancestral characters at selected nodes informs that the group including Atlanticetus and living balaenopterid taxa independently evolved rostra wide at base, anterolateral expansion in the tympanic bulla and a peculiar arrangement of the endocranial foramina of the periotic exhibiting a noteworthy phenomenon of convergent evolution in feeding and hearing functions with Balaenopteridae. The paleobiogeographic analysis showed that the North Pacific was the center of origin of Balaenomorpha (crown mysticetes), Thalassotherii and Balaenoidea. The recurrent invasion of the Mediterranean by balaenomorph mysticetes occurred from both the North Atlantic and North Pacific. Funding provided by: European Community Research Infrastructure Action under the FP 7* Crossref Funder Registry ID: Award Number: BE-TAF 305 and BE-TAF 3057 Funding provided by: Università di Pisa Crossref Funder Registry ID: http://dx.doi.org/10.13039/501100007514 Award Number: Funding provided by: Università degli Studi di Torino Crossref Funder Registry ID: http://dx.doi.org/10.13039/501100006692 Award Number: 2019-UNTODST-0000015 Funding provided by: Università degli Studi di Torino Crossref Funder Registry ID: http://dx.doi.org/10.13039/501100006692 Award Number: ex-60% 2019 Funding ...